PEMBINAN SISWA SMK 1 BATAM MELALUI PENGUATAN KEWIRAUSAHAAN DIGITAL UNTUK MENDORONG PERTUMBUHAN BISNIS BERKELANJUTAN - Muhammad Haldy; Iranda Firiansyah; Vereki Martiano; Riswandi Riswandi; Yujitia Ahdarrijal (ASOSIASI IDEBAHASA KEPRI, 2026)
This community service program aimed to strengthen the digital entrepreneurship competencies of students at SMK Negeri 1 Batam by developing a sustainable entrepreneurship ecosystem. The program addressed students’ limited understanding of digital business, online marketing, and business planning despite their strong interest in entrepreneurship. The activities were conducted through interactive lectures, workshops, participatory learning, discussions, mentoring, and business project assistance involving 30 vocational students. Training materials included digital entrepreneurship, Business Model Canvas (BMC), digital marketing, product branding, social media utilization, and the application of artificial intelligence in business. Program evaluation was carried out through pre- and post-assessments, observations, and participants’ business project presentations. The results showed significant improvements in students’ knowledge, digital business skills, entrepreneurial confidence, and ability to develop business ideas and simple business models. The program also strengthened collaboration between the university and the school, creating a supportive learning environment for digital entrepreneurship. Overall, this initiative demonstrates that digital entrepreneurship training effectively enhances vocational students’ entrepreneurial competencies and supports the development of innovative and sustainable young entrepreneurs.